Follow-up of human cystic echinococcosis by IgE antibodies after albendazole treatment - Vildózola Gonzales, Herman (2015)
Background: In a previous study an IgE ELISA test for hydatidosis was standardized and evidenced high sensitivity (95.6%) and specificity (100%) and encouraging results for the diagnosis and follow up of patients treated with albendazole. Objectives: To confirm efficacy of IgE antibody level determination in patients with cystic echinococcosis treated with albendazole and considered clinically cured and ultrasonographically improved, or recurrence in patients considered improved or cured. Design: Longitudinal, retrospective-prospective, quasi-experimental study, longitudinal study, with pre- and post-test for assessing diagnosis and monitoring in the prospective group, and follow-up and recurrence in both groups. Setting: Instituto de Medicina Tropical "Daniel A. Carrión", Universidad Nacional Mayor de San Marcos, Lima, Peru. Participants: Patients with cystic echinococcosis. Methods: Seventeen patients, 15 female and 2 male, 25-80 years old (average 58 years) carrying one or more hepatic cysts and one also lung cysts were treated with albendazole 12-15 mg/kg in 3 or 5 28-day cycles. One had also surgical treatment for a complication. They were followed for 2 to 12 years after treatment, with clinical and ultrasound evaluation 2-7 times and serum quantification of echinococcosis IgE antibody levels. IgE antibody detection method was IgG ELISA test standardized by the authors. Main outcome measures: Relation of serum IgE antibodies and disease outcome. Results: Out of the 17 patients, 10 had serum IgE below cutoff levels considered as evidence of healing. This coincided with eco structural changes from CE1 and CE2 to CE4 and CE5, according to the ultrasound imaging WHO classification, indicating high activity in the firsts and low or no recent activity in the latter. Seven patients evidencing cure or clinical and ultrasound improvement and significant decrease of IgE some below de cut-off level showed sustained increase of these levels expressing recurrence or appearance of new cysts. Conclusions: ELISA test for cystic echinococcosis IgE antibodies detection standardized by the authors appears as a useful tool for albendazole treatment follow-up in order to confirm clinical and ultrasound cure of liver cystic echinococcosis. It seems also useful for early detection of recurrences in patients cured or markedly improved.